ANALYTICAL AND NUMERICAL SIMULATION FOR THE FORCE OF ADHESION OF REINFORCING ROD WITH CONCRETE (Transport systems and technologies, 2022)
The purpose of this article is to build a mathematical model for calculating the stress-strain state of structural elements of the road pavement. The model is based on the universal function parameter - the force of adhesion of the reinforcing rod to the concrete along their surface contact. It is proposed to define the specified adhesion force as the solution to the simulated boundary value problem. It is shown that it is expedient to use hyperbolic functions to solve such a problem. For the adhesion force, an analytical dependence is obtained, which is a nonlinear function.The proposed model of analysis of the stress-strain state of the reinforcement in comparison with other models is relatively simple. The results of modeling using Maple for the analytical dependence of the adhesion force on the length of the reinforcing rod are shown. It is established that the empirical parameter of the system significantly affects the distribution function of normal stresses. The developed theory will allow design engineers to solve the problem of optimizing pavement structures.
Keywords: differential equations, boundary-value problem, reinforcement bond to concrete, road pavement, stress-strain state.